Arctic Sea Ice in CMIP6. Issue 10 (14th May 2020) - Notz, Dirk; Community, SIMIP
Abstract: We examine CMIP6 simulations of Arctic sea‐ice area and volume. We find that CMIP6 models produce a wide spread of mean Arctic sea‐ice area, capturing the observational estimate within the multimodel ensemble spread. The CMIP6 multimodel ensemble mean provides a more realistic estimate of the sensitivity of September Arctic sea‐ice area to a given amount of anthropogenic CO2 emissions and to a given amount of global warming, compared with earlier CMIP experiments. Still, most CMIP6 models fail to simulate at the same time a plausible evolution of sea‐ice area and of global mean surface temperature. In the vast majority of the available CMIP6 simulations, the Arctic Ocean becomes practically sea‐ice free (sea‐ice area <1 × 10 6  km 2 ) in September for the first time before the Year 2050 in each of the four emission scenarios SSP1‐1.9, SSP1‐2.6, SSP2‐4.5, and SSP5‐8.5 examined here. Plain Language Summary: We examine simulations of Arctic sea ice from the latest generation of global climate models. We find that the observed evolution of Arctic sea‐ice area lies within the spread of model simulations. In particular, the latest generation of models performs better than models from previous generations at simulating the sea‐ice loss for a given amount of CO2 emissions and for a given amount of global warming. In most simulations, the Arctic Ocean becomes practically sea‐ice free (sea‐ice area <1 million km 2 ) in September for the first time before the Year 2050. Key Points: CMIP6 model simulations of Arctic sea‐ice area capture the observational record in the multimodel ensemble spread The sensitivity of Arctic sea ice to changes in the forcing is better captured by CMIP6 models than by CMIP5 and CMIP3 models The majority of available CMIP6 simulations lose most September sea ice for the first time before 2050 in all scenarios